Aplikasi Android Untuk Siswa SMP Materi Bangun Ruang Sisi Datar - Ramadhan Budi Prasetya; Muhammad Baidawi; Fitria Khasanah (Universitas Sarjanawiyata Tamansiswa, 2022)
The rapid improvement of science and generation today has caused many innovations in the use of technological consequences that may facilitate people in learning sports. The splendor of the physical appearance significantly impacts the gaining knowledge of method, the more attractive the media show, the greater prompted college students are to learn it impacts pupil learning effects. The pandemic length demands that pupil learning be done remotely. This studies technique makes use of a qualitative descriptive approach. The statistics collection method consisted of a questionnaire used to discover understanding abilties. topics who meet the criteria in this examine are junior high college students (SMP) in grade 9 with a total of 10 college students. The sampling approach on this studies used purposive sampling. The results confirmed that